EXPERIMENTIAL APPROACHES TO THE STEPS OF THEOFHILOS AND HOMER - Manola, Maria; Vekri, I (E-Journal of Cultural Studies; Volume 14, Number 1, February 2021, 2021)
This study traces the works of the great folk painter Theophilos Hadjimichael of Lesvos, guided by the lights of history, literature, tradition, art and culture, especially in those paintings which place their source of inspiration in the epic poetry of Homer. A story teller grandfather, a “magician”, who "knew how to use words to narrate and plain boards of wood to produce icons of saints", becomes the origin where literature’s experimental approach takes flesh and blood in order to create masterpieces. These works of art had themes taken from grandfather’s stories which allowed the child's mind to imagine heroes, fights and controversies. All these were later imprinted on the canvas of the popular painter. The association of Theophilos with the great epic poet Homer, outlines a tour in places, spaces, verses and paintings starting with the child's experiences, hearings and readings. The main purpose of the suggested tour being to prove the power of the pragmatic experience and to show an imaginary and scientific connection and correlation in the work of the two creators. The themes in several Theophilos' paintings and the verses and intertextual events of the ancient poet seem to be relevant. The testimonies of the personal behavior and social appearance of the unconventional painter reinforce this hypothesis. Keywords: Experimential Approaches, P oet Homer, Painter Theophilos.